ANALISIS IMPLEMENTASI DAN TANTANGAN ETLE DALAM PERSPEKTIF GOOD GOVERNANCE DI INDONESIA - Novasari, Romi Oktarian; Putra, Raniasa; Imania, Katriza; Iriani, Atrika (Universitas Padjadjaran, 2025)
The implementation of ETLE is a police innovation in enforcing traffic laws that utilizes information technology (CCTV cameras) to record violations automatically. This is done to minimize direct interaction between officers and violators, reduce the practice of illegal levies (extortion), and increase transparency. This research discusses how to implement the ETLE system as part of E-Government from a good governance perspective such as accountability, transparency, effectiveness and efficiency in public services and law enforcement. This research aims to analyze the implementation of the Electronic Traffic Law Enforcement (ETLE) system and the challenges faced in realizing the principles of good governance in Indonesia, such as transparency, accountability, effectiveness and efficiency. The implementation of ETLE is part of bureaucratic reform and technology-based traffic law enforcement efforts to reduce direct interactions between officers and violators, which have historically been prone to the practice of illegal levies (extortion). This research uses a descriptive qualitative approach, by collecting data through literature study, observation, and interviews with relevant stakeholders (Polri, Transportation Service, and the community. The research results show that ETLE has great potential in increasing accountability and transparency of law enforcement through clear and systematic digital documentation. This is in line with the principles of good governance. However, in its implementation, there are a number of significant challenges. These challenges include: 1) Infrastructure requirements and large costs, 2) Digital inequality, 3) Identification of violators, 4) Coordination between agencies, 5) Compliance and community culture. This research concludes that although ETLE is a step forward towards good governance in public services, stronger government commitment is needed in improving infrastructure, regulations, outreach and coordination to overcome these challenges effectively. Penerapan ETLE merupakan inovasi kepolisian dalam penegakan hukum lalu lintas yang memanfaatkan teknologi informasi (kamera CCTV) untuk mencatat pelanggaran secara otomatis. Hal ini dilakukan untuk meminimalkan interaksi langsung petugas dengan pelanggar, mengurangi praktik pungutan liar (pungli), dan meningkatkan transparansi.Penelitian ini membahas bagaimana penerapan sistem ETLE sebagai bagian dari E-Government dalam perspektif Good governance seperti akuntabilitas, transparansi, efektivitas, dan efisiensi dalam pelayanan publik dan penegakan hukum. Penelitian ini bertujuan menganalisis implementasi ETLE mampu mewujudkan prinsip-prinsip tata kelola pemerintahan yang baik, seperti transparansi, akuntabilitas, efektivitas, efisiensi, dan keadilan. Penelitian ini menggunakan pendekatan studi kepustakaan (library research), mengkaji berdasarkan literatur review, regulasi, serta hasil penelitian terdahulu yang relevan. Analisis penelitian mengadopsi teori implementasi kebiijakan dari George C. Edwards III yang mengutamakan empat variabel kunci, yaitu komunikasi, sumber daya, disposisi, dan struktur birokrasi. Hasil temuan penelitian ini ialah secara konseptual, ETLE dirancang untuk mendukung prinsip-prinsip Good governance dengan menghadirkan proses penegakan hukum lalu lintas yang lebih cepat, transparan, dan akuntabel. Namun, dalam praktiknya masih terdapat sejumlah kendala, antara lain keterbatasan infrastruktur, rendahnya kesadaran dan penerimaan masyarakat, lemahnya koordinasi antarinstansi, serta minimnya mekanisme pertanggungjawaban atas kegagalan sistem. Kondisi ini menimbulkan kesenjangan antara idealitas kebijakan dengan realitas implementasi di lapangan. Oleh karena itu, diperlukan perbaikan menyeluruh terkait komunikasi, penyediaan sumber daya, penguatan disposisi aparat, dan optimalisasi struktur birokrasi agar sistem ETLE dapat benar-benar mendukung terwujudnya tata kelola pemerintahan yang baik di Indonesia.